2021
DOI: 10.1002/aesr.202000109
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Elemental Inhomogeneity and Its Impact on Ionic Conductivity in Li‐Conducting Garnets Prepared with Different Synthesis Methods

Abstract: Garnet-type lithium lanthanum zirconate (Li 7 La 3 Zr 2 O 12 [LLZO]) and its doped derivatives continue to generate interest as solid electrolytes for future solid-state lithium batteries. Most Li-conducting garnets adopt the cubic garnet crystal structure (Ia3d). [1] However, without extrinsic dopants, LLZO adopts a tetragonal structure (I4 1 /acd) due to its uniquely high Li content, which causes a spontaneous ordering of the Li sublattice. [2][3][4] This thermodynamically favorable (at room temperature) tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 78 publications
(201 reference statements)
0
4
0
Order By: Relevance
“…Second, the deleterious effects of compositional inhomogeneity may be mitigated via the P2G process. Our previous studies on LLZTO showed that inhomogeneous distribution of the Ta-dopant among various grains can lead to lower ionic conductivity and that the P2G method is one approach to mitigate composition inhomogeneity . Not only is compositional uniformity important for achieving high ionic conductivity and stabilization of the cubic phase of LLZTO, but since Zr has been demonstrated to be less stable to reduction by Li metal compared to Ta, , grains with local Zr enrichment could be susceptible to the formation of electronically conducting pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the deleterious effects of compositional inhomogeneity may be mitigated via the P2G process. Our previous studies on LLZTO showed that inhomogeneous distribution of the Ta-dopant among various grains can lead to lower ionic conductivity and that the P2G method is one approach to mitigate composition inhomogeneity . Not only is compositional uniformity important for achieving high ionic conductivity and stabilization of the cubic phase of LLZTO, but since Zr has been demonstrated to be less stable to reduction by Li metal compared to Ta, , grains with local Zr enrichment could be susceptible to the formation of electronically conducting pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al studied MSS systematically in terms of molten salt type, basicity, and washing effect. [35,[95][96][97]114] As shown in Figure 8b, during synthesis, LaOCl was first formed at ≈500 °C and it gradually transformed into La 2 Zr 2 O 7 nanocrystal as temperature increased. Finally, cubic LLZO powder with fine particle sizes of 0.3-3 µm was formed at 900 °C.…”
Section: Wet Chemistry Routes and Other Techniquesmentioning
confidence: 99%
“…[ 4 ] In particular, Ta‐doped lithium lanthanum zirconate garnet, Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 (LLZTO) delivers a high ionic conductivity up to 10 −3 S cm −1 at room temperature, comparable to the values of organic liquid electrolytes used in commercial Li‐ion batteries. [ 5 , 6 , 7 ] With a high shear modulus (≈60 GPa), however, the garnet‐type oxides are typically stiff and very difficult to process. [ 8 ] It is necessary to densify LLZTO pellets to achieve high ionic conductivity and to function as an effective separator, which typically requires high‐temperature sintering treatment (≈1200 °C, 24 h).…”
Section: Introductionmentioning
confidence: 99%